GENESIS OF THEORY AND PRACTICE OF BUDGETING - Grinkevich O.V.; Ivannikov A.E. (Техника и технология пищевых производств, 2015)
Specific and proven management instruments such as budgeting are necessary in the modern conditions of the development of the Russian economy. Its application is needed and approved at any enterprise to increase its efficiency. In this article the historical aspect of the formation and development of budgeting in the Russian economy has been systematized. The historical research method as a kind of the genetic one has been applied. The chronological pereodisation of the genesis of budgeting has been identified, as well as the basic distinctive features of budgeting in these chronological boundaries. Theoretical foundations of budgeting with the necessity to study the identified economic phenomenon during its development have been analysed. Based on European and Russian experience two directions of budgeting development have been identified and the description of their distinctive features has been given. The role and the place of budgeting in the modern business management at Russian enterprises have been outlined. The results of this study will help top-managers of various enterprises of all economic sectors to understand the efficiency of budgeting as an instrument of the strategic and short-term management of the enterprise. Without budgeting, the achievement of competitive power in the market is contingent on coincidence. Dynamically developing enterprises may themselves master the technology of budgeting and develop corresponding documentation.